2014
DOI: 10.1200/jco.2013.53.0808
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-Induced Neurotoxicity and Leukoencephalopathy in Childhood Acute Lymphoblastic Leukemia

Abstract: MTX-related clinical neurotoxicity is transient, and most patients can receive subsequent MTX without recurrence of acute or subacute symptoms. All symptomatic patients and one in five asymptomatic patients develop leukoencephalopathy that can persist until the end of therapy. Polymorphisms in genes related to neurogenesis may contribute to susceptibility to MTX-related neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
301
1
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 303 publications
(329 citation statements)
references
References 43 publications
14
301
1
13
Order By: Relevance
“…In the current cohort, incidence of methotrexate related encephalopathy was 4.8%, and all cases developed neurotoxicity in relation to IT MTX. Comparable incidence was reported by Bhojwani et al [8], who reported 3.8% clinical neurotoxicity, but mostly related to high dose IV MTX [8].…”
Section: Discussionsupporting
confidence: 47%
“…In the current cohort, incidence of methotrexate related encephalopathy was 4.8%, and all cases developed neurotoxicity in relation to IT MTX. Comparable incidence was reported by Bhojwani et al [8], who reported 3.8% clinical neurotoxicity, but mostly related to high dose IV MTX [8].…”
Section: Discussionsupporting
confidence: 47%
“…Leukoencephalopathies immediately following intrathecal methotrexate treatments are a well-known risk (Reddick et al, 2005). There is some indication that susceptibility may relate to particular gene variants, many of which are involved in neurogenesis (Bhojwani et al, 2014). Methotrexate has been shown to disrupt oligodendroglial progenitor cells and phospholipids important for myelination and white matter development (Krull et al, 2013b;Monje and Dietrich, 2012).…”
Section: Figmentioning
confidence: 99%
“…Neuroimaging studies indicate that alterations of brain structure and function represent the final common biological pathway resulting in cognitive deficit. Few neuroimaging studies have been conducted to date, but white matter pathology is the most consistent finding (Bhojwani et al, 2014;Edelmann et al, 2014;ElAlfy et al, 2014;Kesler et al, 2010;Morioka et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…50,99 Despite multiple candidate-gene studies for toxicity, results have been conflicting (or based on single, nonreplicated small studies), and thus it is currently not possible to recommend changes to methotrexate dosing based on inherited variants in these candidate genes. 97,98 Genome-wide studies identified variants associated with leukoencephalopathy, 100 but these findings have not yet been replicated. Methotrexate effects are influenced by interindividual variation in its plasma clearance, leading some to implement an approach that targets systemic exposure based on clearance.…”
Section: Vincristinementioning
confidence: 99%